Pengaruh Komitmen Organisasi, Budaya Organisasi dan Kepemimpinan terhadap Tata Kelola Perusahaan serta Implikasinya pada Kinerja Keuangan Perusahaan - Ester Manik (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2014)
The purpose of the research is to obtain empirical evidence and to find out transparent phenomena as well as conclusions regarding the influence of the organizational commitment, organization culture and transformational leadership toward good corporate governance and its implication on the corporate financial performance of some state owned companies in Indonesia. Organization culture is the major variable that influences good corporate governance in which the dimensions of professionalism and team work have dominantly contributed to organization culture. The second major variable that influences a good corporate governance is the organizational commitment. Transformational leadership becomes the minor variable that influences good corporate governance with its dimensions of intellectual stimulation and individual consideration. In addition, the dimensions of return on equity, current ratio and collecting periods become the most dominant factors/elements of the corporate financial performance. As a result, those state owned companies should optimally improve the ownership structure, organization culture, and transformational leadership including good corporate governance in order to increase the corporate financial performance of those state owned companies.